Students’ Perceptions and Experiences of Using Roblox as A Supporting Tool for English - Aldi Junaidi; Ade Ismail Ramadhan Hamid; Yeni Rahmawati (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study explores students’ perceptions and experiences of using Roblox as a supporting tool for developing English-speaking skills at Universitas Muhammadiyah Kalimantan Timur. Employing a qualitative descriptive research design, the study involved ten participants selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that students generally hold positive perceptions toward the use of Roblox for English-speaking practice, reporting improvements in fluency, confidence, vocabulary, and willingness to communicate in English. Students highlighted that Roblox’s interactive and game-based environment provides authentic opportunities to engage in spontaneous communication with international players, thereby reducing speaking anxiety and increasing motivation. However, challenges such as limited vocabulary, unfamiliar slang, and technical issues were also identified. Despite these obstacles, most participants agreed that integrating Roblox into English learning activities creates a low-pressure, immersive, and enjoyable environment that supports language development. The study concludes that Roblox can serve as an effective supplementary platform for enhancing English-speaking competence and fostering learner autonomy in EFL contexts.